Multi-objective Optimal Design of the MAXDOAS Worm Gear Drive - Shen Wei; Chen Jiexiang; Xu Mingming; Xue Hui; Wang Yong; Wu Yi; Chen Sujuan; Luo Xiaole (Jixie chuandong)
Focus on the problem exiting in the key rotating parts of the worm gear drive on MAX DOAS,the multi- objective optimization model is established,the objective functions is transformed into the evaluation function by using the linear weighted sum method. The objective functions weight coefficient is determined according to importance of demand in engineering application technology. The multi- objective optimization problem is solved and the optimization structure is analyzed to verify the reasonability of the optimization results in one kind of engineering application environment through scientific computing software. The results show that the optimized structure can achieve the design requirements,and the reasonability of the optimization method is proved.